2020
DOI: 10.3390/jcm9010260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Adherence to the Follow-Up Examination after Positive Fecal Occult Blood Test in National Colorectal Cancer Screening

Abstract: Background: The compliance with the follow-up examination after a positive fecal occult blood test (FOBT) is lower than expected. We aimed to evaluate the adherence rate to the follow-up examination in patients with a positive FOBT and to identify the clinical factors associated with this adherence. Methods: The study population comprised adults aged ≥50 years who participated in the National Cancer Screening Program for colorectal cancer (CRC) in 2013. Compliance was defined as undergoing follow-up examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
(42 reference statements)
3
10
0
Order By: Relevance
“…A low rate of follow-up of abnormal FIT/gFOBT has been noted in different studies and different factors were attributed [ 26 30 ]. In our study, most of the patients were referred to a gastroenterologist, but they were not examined or counseled by the gastroenterologist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A low rate of follow-up of abnormal FIT/gFOBT has been noted in different studies and different factors were attributed [ 26 30 ]. In our study, most of the patients were referred to a gastroenterologist, but they were not examined or counseled by the gastroenterologist.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the lack of knowledge about the importance of follow-up which can put the patient at risk of having advanced CRC and increased mortality [ 26 29 ]. Some of the patients’ appointments were missed or not scheduled, which can be due to a lack of communication between the patients and the healthcare system that was addressed in multiple studies [ 30 , 31 ]. A total of 12% of the patients were not informed about the positive FIT/gFOBT, which delays the timely medical intervention, reflecting the essential role of the healthcare provider to ensure follow-up [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from the National Cancer Screening Program in South Korea found that adherence rates to follow-up after a positive faecal occult blood test were associated with being a younger male of high socioeconomic status. 12 For cervical cancer screening, it has been reported that English fluency and number of years in the USA were positively associated with adherence rates. 13 Thus, it is critical for clinicians to recognise these differences, for which interventions may help reduce healthcare disparities.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the number of patients aged below 20 suffering from colorectal cancer was 2.1 times higher than that 10 years earlier, while the number of patients aged above 85 was 3.3 times higher. (5) As a fecal occult blood test (FOBT) effectively screens colorectal cancer, (6) regular health examinations contribute to the early discovery of colorectal cancer, (7) and the immune checkpoint inhibitors should be monitored to treat metastatic colorectal cancer effectively. (8) In terms of the seriousness of cancer cell spread, cancers are classified into stage 0 (carcinoma in situ) and stages I-IV.…”
Section: Introductionmentioning
confidence: 99%